Knowledge, attitude and practice towards multiple myeloma among medical staff in Enshi Region - Luping Zou; Jinhua Li; Hang Xiang; Jun Tan; Yan Zeng (Scientific Reports)
Abstract A study in the Enshi Region between Sept-Nov 2023 assessed medical staff’s knowledge, attitude, and practice regarding multiple myeloma. The disease significantly impacts physical health, quality of life, and mental well-being. Medical professionals play crucial roles in its prevention and treatment. Analysis used Pearson’s correlation, logistic regression, and structural equation model (SEM). A total of 229 valid questionnaires were collected, with 68.6% of female participants, and 42.4% aged 31–40 years. The knowledge, attitude, and practice scores were 36.27 ± 4.97 (range: 25–53), 42.40 ± 5.78 (range: 30–56), and 29.71 ± 6.41 (range: 7–35), respectively. Pearson’s correlation analysis revealed significantly positive correlation between knowledge and attitude. Moreover, in both univariate and multivariate analysis, knowledge showed positive association with attitude. Several demographic factors independently associated with KAP scores were identified, including education level, age, occupation type, and frequency of academic conferences or medical education activities per year. SEM further indicated direct association between attitude and practice (β = 0.320, 95%CI: 0.189–0.452, P < 0.001). In the Enshi Region, medical staff displayed moderate knowledge, neutral attitudes, and proactive practices towards multiple myeloma. Moreover, significant positive association was found between knowledge and attitude. These discoveries provided valuable perspectives to the development of healthcare interventions and educational initiatives for improving medical staff’s knowledge, attitudes, and practices.